2017
DOI: 10.1038/s41598-017-00977-0
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 7 deficiency protects apolipoprotein E-deficient mice from diet-induced atherosclerosis

Abstract: Toll-like receptor 7 (TLR7) mediates autoantigen and viral RNA-induced cytokine production. Increased TLR7 expression in human atherosclerotic lesions suggests its involvement in atherogenesis. Here we demonstrated TLR7 expression in macrophages, smooth muscle cells (SMCs), and endothelial cells from mouse atherosclerotic lesions. To test a direct participation of TLR7 in atherosclerosis, we crossbred TLR7-deficient (Tlr7 −/−) mice with apolipoprotein E-deficient (Apoe −/−) mice and produced Apoe −/− Tlr7 −/− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 90 publications
1
15
0
Order By: Relevance
“…16) In contrast, Liu, et al demonstrated a detrimental role for TLR7 in diet-induced atherosclerosis in ApoE −/− mice by showing an increase in lesion inflammation (MHC-II), lesion proinflammatory cytokine expression (IL-6), lesion protease expression (CatS and MMP-9), and systemic inflammation (plasma). 6) In agreement with these findings, we show that the pro-inflammatory stimulation of TLR7 by high concentrations of R848 impairs reendothelialization following acute vascular injury combined with increased levels of EMPs, induced Sca1/Flk1 positive cells, and elevated levels of IL-6 and RANTES. TLR7 activation in WT mice induced a systemic inflammatory reaction and disturbed the regeneration of endothelial cells after injury.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…16) In contrast, Liu, et al demonstrated a detrimental role for TLR7 in diet-induced atherosclerosis in ApoE −/− mice by showing an increase in lesion inflammation (MHC-II), lesion proinflammatory cytokine expression (IL-6), lesion protease expression (CatS and MMP-9), and systemic inflammation (plasma). 6) In agreement with these findings, we show that the pro-inflammatory stimulation of TLR7 by high concentrations of R848 impairs reendothelialization following acute vascular injury combined with increased levels of EMPs, induced Sca1/Flk1 positive cells, and elevated levels of IL-6 and RANTES. TLR7 activation in WT mice induced a systemic inflammatory reaction and disturbed the regeneration of endothelial cells after injury.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, Liu, et al demonstrated a pro-inflammatory role for TLR7 in atherogenic diet-induced atherosclerosis in apolipoprotein E-deficient (ApoE −/− ) mice. 6) To further investigate the role of TLR7 in atherosclerosis, we stimulated TLR7 using the R848 ligand in vitro, as well as in acute and chronic vascular injury experiments in vivo.…”
mentioning
confidence: 99%
“…Chronic dysregulated TLR activation has been reported in a plethora of non-infectious pathologies and autoimmune diseases, including CVD [84,85], atherosclerosis [86,87], and type-2 diabetes [88,89]. As demonstrated by animal TLR knockout models [90][91][92][93][94][95][96] and studies involving TLR deficiency [97,98] and polymorphisms in humans [99][100][101][102][103][104][105][106][107][108][109][110][111], absence or improper function of TLRs can attenuate inflammation, influence disease susceptibility, and restore homeostatic balance. Thus, TLRs have become targets of TLR inhibition therapies [112][113][114][115][116].…”
Section: Taurine Toll-like Receptors and Cardiovascular Diseasementioning
confidence: 99%
“…The first study reported from Salagianni et al showed a protective effect for TLR7 in atherosclerosis through a macrophage shift towards a repair-healing subtype [9]. In contrast, Liu et al indicated that TLR7 has a detrimental role [24]. The discrepancy in these two studies might be explained by the use of different diet.…”
Section: Discussionmentioning
confidence: 99%